Gerakan Pencegahan Stunting Kukerta UNRI Melalui Edukasi Pada Masyarakat Di Kampung Sungai Kayu Ara Kabupaten Siak - Efriyeldi Efriyeldi; Sonya Marunjung P.Hsb; Destriana Destriana; Fazli Pasha Amri; Hesty Widyaningsih; Wulan Cempaka Sari.S; Mia Fatma R; Inel Vivi Elvia; Dela Haryani; Naufal Sidqi; Ilham hidayat (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Stunting is a problem of chronic malnutrition caused by a lack of nutritional intake over a long period of time due to the provision of food that is not in accordance with nutritional needs. The aim of this activity is to educate the people of Sungai Kayu Ara village regarding the importance of stunting. This socialization activity broadens the mothers' insight so that anticipatory preparations for stunting prevention can be carried out from the start. The implementation method in this research is an educational approach, direct interaction with the community, evaluation of knowledge before and after socialization, as well as concrete actions to improve children's nutrition. All of these efforts aim to increase the community's understanding of stunting and provide concrete support to prevent it. The data sources used in this research are interviews, questionnaires and observations. The results of this research are that the majority of the people of Sungai Kayu Ara Village still have little understanding about stunting can be seen from the results of the questionnaire that was distributed by Kukerta Unri students. Of the 35 respondents who were distributed the questionnaire, only around 12 people understood about stunting. Therefore, socialization is needed regarding stunting, the effects it causes, how to prevent it, and efforts to overcome stunting from The most basic stage, as a form of individual preparation effort without relying on government programs, because overcoming stunting is an urgent problem that must be handled by various parties.